Complement Component C3: A Novel Biomarker Participating in the Pathogenesis of Non-alcoholic Fatty Liver Disease - Han, Juqiang; Zhang, Xiang (Frontiers in Medicine, 2021)
Non-alcoholic fatty liver disease (NAFLD) is currently the most common cause of chronic liver disorder worldwide. The pathological spectrum of NAFLD ranges from simple steatosis to non-alcoholic steatohepatitis (NASH) that induces progressive liver cirrhosis and eventually hepatocellular carcinoma (HCC). However, the molecular mechanisms driving the transformation of NASH are obscure. There is a compelling need for understanding the pathogenic mechanisms of NASH, and thereby providing new insight into mechanism-based therapy. Currently, several studies reported that complement system, an innate immune system, played an important role in the pathogenesis of NAFLD, which was also proved by our recent study. Complement component 3 (C3), a protein of the innate immune system, plays a hub role in the complement system. Herein, we present a review on the role and molecular mechanism of C3 in NASH as well as its implication in NASH diagnosis and treatment.